Synthesis of pyrazolo[1, 5-a]quinoxalin-4(5H)-ones via one-pot amidation/N-arylation reactions under transition metal-free conditions. Issue 37 (26th August 2016) - Wiethan, Carson; Franceschini, Steffany Z.; Bonacorso, Helio G.; Stradiotto, Mark
Abstract : An efficient one-pot procedure for the synthesis of new pyrazolo[1, 5- a ]quinoxalin-4(5 H )-ones from easily prepared 1-(2-chlorophenyl-5-ethylcarboxylate)pyrazoles and various primary alkylamines is described. Abstract : An efficient one-pot transition metal-free procedure for the synthesis of new pyrazolo[1, 5- a ]quinoxalin-4(5 H )-ones from easily prepared 1-(2-chlorophenyl-5-ethylcarboxylate)pyrazoles and various primary alkylamines is described. The key steps involved in the synthesis of the new 5, 6-fused ring system are the formation of an amide intermediate followed by an intramolecular N -arylation reaction via nucleophilic aromatic substitution.